FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENJADI KONSULTAN JAFRA INDONESIA - Annisya Winarni Putri (Media Bina Ilmiah, 2023)
JAFRA Cosmetics is a business with a multilevel- marketing model that focuses on selling beauty products such as skincare and makeup. In an effort to expand its business network, JAFRA consultants recruit new members by relying on persuasion skills. This study aims to determine what factors influence a person's interest in becoming a JAFRA consultant. This research is a phenomenological research using literature study data collection techniques. The results of this study are that there are several main factors that influence an individual's interest in becoming a Jafra Indonesia consultant, namely: getting direct profits from sales, receiving free marketing training, and liking uplines who invite them to join